PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI DAN BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASI UNIT AKTIVITAS MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ISLAM MALANG - Kholid Kholid; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT This study aims to study the style of leadership, communication, and culture towards commitment to the Student Activity Unit of the Faculty of Economics and Business. While the variables used in this study are commitment variables as dependent variables, while the independent variables are leadership style, communication, and organizational culture. Data was collected through a questionnaire method with the number of samples used as respondents as many as 81 respondents. The results of this study simultaneously conclude that there is an influence between leadership style, communication and organizational culture variables on commitment and partially concludes that there is an influence between leadership style, communication and organizational culture variables on commitment. Keywords: commitment, leadership style, communication, organizational culture